The moderating role of entrepreneurship education in shaping entrepreneurial intentions - Iqtidar A. Shah; Sohail Amjed; Said Jaboob (Journal of Economic Structures, 2020)
Few studies investigated the role of entrepreneurship education in students' entrepreneurial intentions. These studies produced controversial results which invited the attention of researchers for further investigations. This paper examines the moderating role of entrepreneurship education on the predictive value of attitude, subjective norms and self-efficacy for entrepreneurial intentions. True Experimental Design (post-test-only control group design) is used to investigate the change in the nature and magnitude of the impact of independent variables (personal attitude, self-efficacy and subjective norms) on the dependent variable (intentions) using entrepreneurship education as a moderating variable. Data were collected from the treatment group (completed entrepreneurship course) and control group (not taken entrepreneur-ship course) from various higher education institutions in Oman. Total 500 question-naires were distributed, out of which 204 filled questionnaires were received back in which 196 qualified as valid responses. Structural equation modeling was used to test hypotheses. The statistical relationship among the modeled variables was estimated using Partial Least Square method. The results revealed that attitude toward entrepreneurship, subjective norms and self-efficacy are the significant predictors of entrepreneurial intentions. However, entrepreneurship education moderates this relationship by strengthening the path coefficients of attitude toward entrepreneurship and self-efficacy. Same time it weakens the path coefficient of subjective norms.
Keywords: 330; Attitude; Entrepreneurship; Intention; Knowledge; Pre-experimental design; Skills